“Saya Takut Tidak Bisa Jadi Guru yang Baik”: Refleksi Kecemasan Mengajar Mahasiswa Calon Guru - Sitti Nurfaidah (Institut Agama Islam Negeri Kendari, 2018)
This case study aims to examine and discuss preservice teachers’ anxiety in facing real classrooms during their field teaching program. This study was exploratory and interpretive in nature. Data were collected from ten student teachers’ reflective teaching journal and in-depth interview. The participants were assigned to teach Islamic Religious subject at one of high schools at Kota Kendari. Results of the study indicate that the participants’ anxiety was overwhelmed at their first day at the school. Their nervousness, however, was gradually reduced as the program went on when they were involved in school observation and administrative tasks at the first two weeks. Upon teaching the real classroom for the first time, they were filled with more apprehension; the fear of not being able to deliver material well and not being able to be a good teacher were amongst their worries. This preliminary study implies the need for further and comprehensive empirical study on psychological factors the student teachers might encounter during their field teaching program and how this concern is accommodated by the teacher education program.